Comparison of Plaque Inhibiting Efficacies of Aloe Vera and Propolis Tooth Gels: A Randomized PCR Study - Kumar, Aravind (J Clin Diagn Res, 2015)
BACKGOUND AND AIM: Allopathic medications used for periodontal disease are known to be associated with various side effects. Hence a search for naturotherapies are on the rise. Among the natural pharmacons available aloevera and propolis are considered to be effective and free from adverse effects. Taking this into account, the present study was done to compare the plaque inhibiting efficacies of Aloe vera and Propolis tooth gels in patients with chronic periodontitis. MATERIALS AND METHODS: Forty patients diagnosed with chronic periodontitis were randomly allocated to groups A and B containing 20 patients each. Patients in group A were advised to use Aloe vera tooth gel while those in group B were advised to use Propolis tooth gel. Clinical and microbiologic parameters using Polymerase chain reaction (PCR) were recorded at baseline and after 3 months. RESULTS: Student t-test was performed for all the obtained results. In the Aloe vera group, comparison of baseline PCR and after 3 month results showed reduction only in P. gingivalis (p=0.001), where as statistically significant reduction in all the three red complex microorganisms was seen in propolis group. All the clinical parameters (Plaque Index, Gingival Index, Bleeding on Probing, Probing pocket Depth, and Clinical Attachment Level) in both the groups showed statistically significant reductions after 3 months. CONCLUSION: Propolis showed a statistically significant reduction in plaque, microbiologic and clinical parameters. However, clinical trials of longer durations with larger sample sizes are required to evaluate the efficacy.